Influence of Dexamethasone Premedication on Acute Lung Toxicity in Lung SBRT - Alite, Fiori; Shaikh, Parvez M.; Mahadevan, Anand (Frontiers in Oncology, 2022)
Introduction The cooperative group experience of thoracic sterotactic body radiation therapy (SBRT) in medically inoperable patients with early stage non-small cell lung cancer (NSCLC) historically utilized corticosteroid premedication. Patterns of care have been mixed as to whether premedication adds benefit in terms of improved lung toxicity and treatment tolerance. Methods Patients treated for NSCLC from 2014 to 2017 with definitive thoracic SBRT (BED10≥100) at a single institution, in a prospectively collected database were evaluated. Pretreatment clinicopathologic characteristics, including Eastern Cooperative Oncology Group (ECOG) performance status, PFT parameters of FEV1, and diffusing capacity for carbon monoxide (DLCO) were collected. Treatment and dosimetric characteristics were collected, and patients were scored as to whether dexamethasone was prescribed and utilized with each fraction. Toxicity was graded on multiple domains including lung as during and 30 days after completion of treatment using Common Terminology Criteria for Adverse Events Version 4. Univariate analysis was performed with Fisher’s exact test for categorical variables and two-tailed Student’s t-test for continuous variables. Multivariate analysis was performed with Cox proportional hazards model to adjust for age, pretreatment DLCO, ECOG, tumor size, central versus peripheral location, and biological effective dose. Results A total of 86 patients treated with thoracic SBRT with 54–60 Gy in 3–8 fractions met inclusion criteria, with the majority (70%) receiving 5 fractions. Of these patients, 45 (52%) received 4 mg dexamethasone premedication prior to each fraction of SBRT and 41 (48%) were treated without dexamethasone premedication. Overall acute lung toxicity was low in both groups. Between the two groups of patients, 5/45 (11%) developed grade 2 or higher lung toxicity including hospital admission in the dexamethasone premedication arm vs. 2/41 (5%) without premedication (p = 0.4370, Fisher’s exact test). Freedom from acute SBRT lung toxicity was no different between dexamethasone premedication arm and no premedication (Log rank, p = 0.45). On multivariate Cox proportional hazard modeling adjusting for age, ECOG, tumor size, central vs. peripheral location, pretreatment DLCO, and BED, there was no difference in freedom from acute lung toxicity without dexamethasone premedication (HR: 0.305; 95% CI: 0.033, 2.792; p = 0.293). Conclusions In this retrospective analysis, pretreatment steroid prophylaxis with dexamethasone confers a similar acute toxicity profile and no added clinical benefit to treatment without pretreatment steroid prophylaxis.